Contrast-enhanced dual-energy mammography: a promising new imaging tool in breast cancer detection. (May 2014) - Lalji, Ulrich; Lobbes, Marc
Contrast-enhanced dual-energy mammography (CEDM) is a promising new breast imaging tool for breast cancer detection. In CEDM, an iodine-based contrast agent is intravenously administered and subsequently, dual-energy mammography is performed. This results in a set of images containing both a regular mammogram and an image that contains contrast enhancement information. Preliminary studies have indicated that CEDM is superior to conventional mammography and might even match the diagnostic performance of breast MRI. In this review, the imaging technique, protocol and patient handling of CEDM is presented. Furthermore, an overview of current results on CEDM and potential future indications are outlined.